Physical activity, lung function, and sleep outcomes in urban children with asthma. Issue 7 (12th April 2021) - Powers, Kate E.; Jelalian, Elissa; Dunsiger, Shira; Farrow, Michael; Miranda, Luis G.; Mitchell, Patricia; Kopel, Sheryl; Koinis‐Mitchell, Daphne
Abstract: Objectives: To examine (1) whether daily declines in physical activity (PA) level and/or in lung function (FEV1) predict an asthma exacerbation in a sample of urban children with asthma, and (2) the association between number of sleep awakenings and decline in daytime PA in this group. Methods: In this sample of urban children aged 7–9 years with persistent asthma ( N = 147), objective methods assessing lung function via a handheld spirometer and moderate‐to‐vigorous physical activity (MVPA) via accelerometry were measured over a 4‐week period during the fall and early winter of each year as part of a larger 5‐year study. Results: In the entire sample, a significant association between PA and lung function was noted such that a greater decline in daily MVPA was associated with lower odds of exacerbation. Ethnic group differences showed that this association was also significant only among Latino children (odds ratio [OR] = 0.98; 95% confidence interval [CI]:0.97–0.99). A greater number of sleep awakenings were associated with greater declines in daily MVPA among Latinos only ( p = .05). Conclusions: Results suggest that declining MVPA may contribute to lower risk for an exacerbation. Reasons for declining MVPA need to be further explored in this group. Children with asthma may avoid or be fearful of engaging in PA or may face early symptoms which influence patterns of PA, and this may minimize risk for an exacerbation. Results also suggest reasons for night‐time disruptions may need to be targeted in further research or interventions as they can contribute to PA avoidance in this high‐risk group.